Enhancing Childrens Cognitive Abilities Through â€œJelajah Alamâ€ Apllication : Promoting Well-being - Mariyati, Lely Ika; Fahmawati, Zaki Nur; Indahyanti, Uce; Pertiwi, Berlian Putri; Putra, Rolando Jordan Permana (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The use of technology in the early childhood learning process is rarely found despite the numerous benefits it offers. This study aimed to examine the effectiveness of the